Implementasi Kebijakan tentang Sistem Kerja Perangkat Daerah Kabupaten Buleleng (Studi Kasus Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu) - Shinta Brafiana Putri; Sofjan Aripin; Andi Wijaya Aripin (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
This study aims to analyze the implementation of regional government work system policies following bureaucratic simplification in Buleleng Regency. The case study was conducted at the Investment and One-Stop Integrated Service Office (DPMPTSP), as it is the regional work unit directly affected by organizational restructuring. The background of this research includes employee resistance, inconsistencies between documents and regulations, and the suboptimal use of technology. This study employs a descriptive qualitative approach using a case study method and is analyzed based on Edward III’s policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure. The results indicate that although regulations and technological support are already in place, the implementation of the new work system still faces several challenges. These include the persistence of traditional work culture, the underutilization of applications for cross-unit collaboration, limited understanding among employees regarding the squad team system, and suboptimal standard operating procedures. In addition, limited budgets and human resources also pose major obstacles. The increase in the Public Satisfaction Index (PSI) from 82.41 in 2022 to 84.26 in 2024 demonstrates the positive impact of implementing work system policies on the quality of public services at the DPMPTSP of Buleleng Regency. Therefore, continuous innovation and improvement are necessary to achieve a more efficient, collaborative bureaucracy that is oriented toward high-quality public service.